Infective endocarditis of a rare etiology: Serratia marcescens - Đokić Milomir; Milanović Milomir; Begović Vesna; Ristić-Anđelkov Anđelka; Tomanović Branka (Vojnosanitetski Pregled)
Infective endocarditis (IE) is a unique diagnostic and therapeutic challenge. It is a severe disease, fatal before penicillin discovery. Atypical presentations frequently led to delayed diagnosis and poor outcome. There was little information about the natural history of the vegetations during medical treatment or the relation of morphologic changes in vegetation to late complications. Application of a new diagnostic criteria and echocardiography, increased the number of definite diagnosis. Trans-thoracic and trans-esophageal echocardiography had an established role in the management of patients with IE. The evolution of vegetation size, its mobility, and consistency, the extent of the disease, and the severity of valvular regurgutation were related to late complications. With therapeutic options including modern antibiotic treatment and early surgical intervention IE turned out to be a curable disease. Reduction in mortality also depended on prevention. Antibiotic prophylaxis of IE was important, but low mortality was also the result of early treatment, especially in the event of early recognition of symptoms and signs of the disease.